Sosialisasi tentang Peran Gen Z dalam Memerangi Korupsi di SMA Negeri 10 Latuhalat Kota Ambon - Anwar, Arman; Lapelelo, Nadya Putri Firdiana; Ratmin, Nanda Riyani; Putri, Maulidya Handayani Suita (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Corruption in Indonesia is increasing so much that the President has declared war against corruption. Anti-corruption education has an important role in fighting corruption. One effort that can be done is to provide outreach to Gen Z so that they can take this role in fighting corruption. Gen Z's involvement in social issues is becoming increasingly evident with their ability to disseminate information quickly through online platforms, so that it can be significantly useful in preventing and eradicating corruption.Purposes of Devotion: To improve and motivate students to play a role of eradicating corruption in accordance with the characteristics and advantages possessed by Gen Z. Method of Devotion: It was carried out through a luring with lecture , then continued with an interactive discussion where participants had the opportunity to ask questions and answers regarding the role of Gen Z in fighting corruption according to the characteristics and advantages they have.Results of the Devotion: Students at SMA Negeri 10 Ambon become more aware of the importance of anti-corruption education in forming anti-corruption character and become more concerned about efforts to eradicate corruption. The potential of students as Gen Z who have intelligence in mastering and using communication and information technology and various other advantages they have, can be used to play an important role in preventing and eradicating corruption both in the family, environment and in a wider scope. Their ability to disseminate information quickly through online platforms, such as using social media as a means to share opinions, voice aspirations and mobilize support, can be useful in eradicating corruption. This makes Gen Z a potential force in fighting for integrity and transparency in government and public institutions. Educational measures, empowerment and support for anti-corruption initiatives can further strengthen the positive role of Gen Z in maintaining the integrity and welfare of society as a whole.